If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -36 + 2x = -4 + -2x Reorder the terms: -36 + 12x + 2x = -4 + -2x Combine like terms: 12x + 2x = 14x -36 + 14x = -4 + -2x Solving -36 + 14x = -4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -36 + 14x + 2x = -4 + -2x + 2x Combine like terms: 14x + 2x = 16x -36 + 16x = -4 + -2x + 2x Combine like terms: -2x + 2x = 0 -36 + 16x = -4 + 0 -36 + 16x = -4 Add '36' to each side of the equation. -36 + 36 + 16x = -4 + 36 Combine like terms: -36 + 36 = 0 0 + 16x = -4 + 36 16x = -4 + 36 Combine like terms: -4 + 36 = 32 16x = 32 Divide each side by '16'. x = 2 Simplifying x = 2
| 2-4x=30 | | 2(x-2)=-5(3-x)-1 | | 5(x-2)-(7x-12)=x+1 | | 139-2x=34x+15 | | 8x-(6x-1)=2 | | x-2-5=11 | | 3(2x-1)=4x-5 | | 3x-6=2x+6 | | 4x+2=3x+4 | | 12-7x=127-42x | | 16-3x=-24-7x | | 0.4x+0.5(30)=0.3(x+40) | | 151-5x=5x+21 | | -6=4z | | -24-5x=8-9x | | -7r+6t-s-5r+s+4t-6t+5s-r= | | 9-4x=2x | | 2y^3-(4y^2)-5=0 | | 7-x=2x+7 | | 7-x=2x-7 | | 2y^3-4y^2-5= | | 0.08(50)+0.40x=0.20(50+x) | | 9-4x=2x(3)+6 | | -3x+2=2 | | 10x-5=95 | | 2y^3-(4y^2)-5= | | 9-4x=2(3)+6 | | 4x-9x=5.5 | | 3x+6=4x+5 | | 3x+9=4x+3 | | 10-4d=-6 | | -9x^2-5x+1=0 |